2018
DOI: 10.1038/s41598-018-28551-2
|View full text |Cite
|
Sign up to set email alerts
|

The serrulatane diterpenoid natural products RAD288 and RAD289 stimulate properties of olfactory ensheathing cells useful for neural repair therapies

Abstract: Olfactory ensheathing cells (OECs) are being trialled for cell transplantation therapies for neural repair as they have unique properties which can enhance neuron regeneration. However, improvements in cell viability, proliferation and migration are needed to enhance therapeutic outcomes. Growth factors can enhance cell activity, but they can also induce side effects as they can act on numerous cell types. An alternative approach is to identify natural products (NPs) that more selectively activate specific cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…We have previously identified that two serrulatane diterpenoid natural products, RAD288 (3-acetoxy-7,8-dihydroxyserrulat-14-en-19-oic acid) and RAD289 (3,7,8-trihydroxyserrulat-14-en-19-oic, Fig. 1a), stimulate viability of OECs, in particular RAD289 15 . We therefore used RAD289 as a positive control and tested RAD289 and RAD618 using the same viability assay which confirmed that RAD618 strongly stimulated the cell viability (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously identified that two serrulatane diterpenoid natural products, RAD288 (3-acetoxy-7,8-dihydroxyserrulat-14-en-19-oic acid) and RAD289 (3,7,8-trihydroxyserrulat-14-en-19-oic, Fig. 1a), stimulate viability of OECs, in particular RAD289 15 . We therefore used RAD289 as a positive control and tested RAD289 and RAD618 using the same viability assay which confirmed that RAD618 strongly stimulated the cell viability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that natural compounds can stimulate OEC viability. These include curcumin from turmeric 13 , linckosides from starfish 14 and two serrulatane diterpenoids from the Australian desert plant Eremophila microtheca 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies began to adopt the standard wound healing assay for screening multi-phenotypic responses of compounds with polypharmacologic effects 13 . Other studies tried to investigate the effect of compounds or natural extract by integrating results from two independent phenotypic assays including both cell viability assay and wound healing assay 7,8,14,15 . However, such previous studies still required the primary screening to eliminate false positive compound with cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The transplanted cells are thought to promote regeneration by secreting growth factors and guidance factors, by providing physical support, and by clearing debris arising from dead cells 13,15 . It has also been suggested that stimulation of the phagocytic activity to more rapidly clear the injury site of cell debris will further promote regeneration 13,[17][18][19][20][21] . To date, it remains unknown how peripheral glia recognize, internalize and process necrotic targets.…”
mentioning
confidence: 99%